Peningkatan Hasil Belajar Peserta Didik Menggunakan Model Snowball Throwing pada Materi Unsur-Unsur Bangun Datar di Kelas III SDN 10 Koto Baru - Nabila, Dwike Rahmi; Ahmad, Syafri; Ningsih, Yarisda; Sartono, Sartono (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to describe the improvement of student learning outcomes using the Snowball Throwing model in Mathematics learning in class III SDN 10 Koto Baru. This study is a Classroom Action Research (CAR) using a qualitative approach carried out in two cycles. Each cycle consists of planning, implementation, observation and reflection. The subjects in this study were teachers and students of class III SDN 10 Koto Baru totaling 13 people in the January-June semester of the 2024/2025 academic year. The research data were in the form of observations of teaching modules, observations of teacher and student activities, and student learning outcomes using the Snowball Throwing model. Data collection techniques were in the form of observation analysis, tests and non-tests. The results of observations of teaching module planning in cycle I were 89.58% (SB), increasing in cycle II to 95.31% (SB). The results of observations of teacher aspects in cycle I were 85.71% (B), increasing in cycle II to 96.42% (SB). The results of observations of student aspects in cycle I were 5.71% (B), increasing in cycle II to 96.42% (SB). Student learning outcomes in cycle I were 76.5 (C), increasing in cycle II to 84.63% (B). Thus, the study shows that the Snowball Throwing model can improve student learning outcomes in Mathematics learning in class III of SDN 10 Koto Baru.